Improving Elementary Students' Critical Thinking Skills Through Guided Discovery Learning Assisted by Interactive PowerPoint Media: A Classroom Action Research - Adi Syaputra; Megawati Megawati; Antok Kurniawan (Journal of Educational Sciences, 2026)
Critical thinking is one of the most vital competencies demanded by twenty-first-century education. However, a preliminary assessment at SD Negeri 84/II Empelu revealed that only 15% of fourth-grade students met established critical thinking criteria, reflecting persistent teacher-centered instructional practices. This classroom action research aimed to determine whether the implementation of the Guided Discovery Learning model assisted by interactive PowerPoint media could improve students' critical thinking skills. The study followed the Kemmis and McTaggart spiral model across two cycles with four instructional meetings, involving 20 fourth-grade students selected through purposive sampling. Data were collected through critical thinking essay tests and structured teacher and student observation sheets, then analyzed descriptively with a predetermined success criterion of at least 80% classical mastery. Results showed a progressive improvement in student mastery from 15% at baseline to 60% in Cycle I and 85% in Cycle II, surpassing the success criterion, with all five critical thinking indicators reaching the very good category by the final cycle. These findings confirm that integrating Guided Discovery Learning with interactive PowerPoint media effectively promotes critical thinking development in elementary school classrooms.